-13x+16=16x-9

Simple and best practice solution for -13x+16=16x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13x+16=16x-9 equation:


Simplifying
-13x + 16 = 16x + -9

Reorder the terms:
16 + -13x = 16x + -9

Reorder the terms:
16 + -13x = -9 + 16x

Solving
16 + -13x = -9 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
16 + -13x + -16x = -9 + 16x + -16x

Combine like terms: -13x + -16x = -29x
16 + -29x = -9 + 16x + -16x

Combine like terms: 16x + -16x = 0
16 + -29x = -9 + 0
16 + -29x = -9

Add '-16' to each side of the equation.
16 + -16 + -29x = -9 + -16

Combine like terms: 16 + -16 = 0
0 + -29x = -9 + -16
-29x = -9 + -16

Combine like terms: -9 + -16 = -25
-29x = -25

Divide each side by '-29'.
x = 0.8620689655

Simplifying
x = 0.8620689655

See similar equations:

| 2a-21.9=A+1.1 | | -40+8n=8(2+8n) | | 5ln(x+16)=1 | | 0=10X^2+30X-9 | | -13x+16=13x-9 | | 42=4w+3w | | V/8=-19/8 | | 6a-4=4a+32 | | -3y+4=8 | | 18x+(-6)=9 | | 74=d+34 | | -13x+16=-16x+16 | | 12+27= | | 4x-6+2x=60 | | z/20=1 | | 4=6p-7p | | -13x+16=13x+16 | | 3r-12=9 | | -13x+16=-13x-9 | | 13/x=1 | | 1=2s-3 | | 19x+9=-7 | | 49-64x=0 | | 10.5+-12.4=-12.4+10.72 | | -13x+16=-13x+11 | | -1.6=4+7 | | 6=9x-12 | | 4/5=20/ | | -13x+16=-13x+16 | | 4x^2-1=5x+3 | | 10x+(-6)=10 | | z+12=27 |

Equations solver categories